(3eaGJjM GdLfGf heUGHjM GdLfGfs - (3GdHQShj GdMfaj, jYbhH Hf Ydj, J (B931 (3g` s
(3ChdgG (B:s
(3MeOG def ef Ydi YHGOg fYeI GdESdGe (B((3cPG(B) (3hLYdg TQYI hefgGLG hfUH GdcJGH hGdSfI CeGeg SQGLG hgGLG bGd GdeUfa(B: (3CYfj GdaGVd GdgeGe JbjO GdCFeI GdcQGe GdTgjQ Hjfge HQcf GdESdGe(B: (3CMeO Gddg GdPj OdfG (B() (3Ydi GdcQjb Cj CQTOfG Ydi eYQaJg HGdThGgOs
(3BNQgG (B:s
(3fGbU GdBNQ, hjfJgj YfO bhdg(B: (3JSgjd TQM JMaI Gdedhc , efjI GdeaJj, fhGRd aJGhi CHj GddjK, TQM bOhQj (B() (3ebOeI ZRfhjI LhGgQ (B((3EjKGQ(B) (3cPG TQM eNJGQ RjdYj aJGhi XgQjI JJeI GdaJGhi TQM WMGhj aJGhi JGJGQNGfjI eLeY GdaJGhis
(3gPG GdTQM eeRhL HGdeJf GdCUd GdeTQhM, hbO hVYJ NWhW HGddhf GdCMeQ ahb cdeGJ GdeJf GdCUdjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 201s
(3eYLe GdeDdajf(B: 4 / 130s
(3cTa GdXfhf(B: 2 / 1044s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs